1997
DOI: 10.1093/nar/25.22.4599
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 2'-O-Me(CGCGCG)2, an RNA duplex at 1.30 A resolution. Hydration pattern of 2'-O-methylated RNA

Abstract: The molecular and crystal structure of 2'-O-Me (CGCGCG)2 has been determined using synchrotron radiation at near-atomic resolution (1.30 A), the highest resolution to date in the RNA field. The crystal structure is a half-turn A-type helix with some helical parameters deviating from canonical A-RNA, such as low base pair rise, elevated helical twist and inclination angles. In CG steps, inter-strand guanines are parallel while cytosines are not parallel. In steps GC this motif is reversed. This type of regulari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 37 publications
5
46
0
Order By: Relevance
“…The X-ray crystal and NMR solution structural studies of this duplex showed that the 2′-OMe group points towards the minor group (43–45) and is very close to the H5′ of the 3′-neighboring residue (43). The X-ray structure of the fully modified, r(CGCGCG) 2 duplex shows that the 2′-OMe group affects the minor groove hydration pattern (44,45), thus stabilization of the U-3·A24 base pair may arise from protection of the 2′-OMe group from water. Previous studies showed that a 2′-OMe modification at U-3 increased the undocking rate of the P1 duplex by ∼140-fold (7).…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray crystal and NMR solution structural studies of this duplex showed that the 2′-OMe group points towards the minor group (43–45) and is very close to the H5′ of the 3′-neighboring residue (43). The X-ray structure of the fully modified, r(CGCGCG) 2 duplex shows that the 2′-OMe group affects the minor groove hydration pattern (44,45), thus stabilization of the U-3·A24 base pair may arise from protection of the 2′-OMe group from water. Previous studies showed that a 2′-OMe modification at U-3 increased the undocking rate of the P1 duplex by ∼140-fold (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although the 2%-oxygens of both modified residues formed contacts to water molecules, the corresponding distances were relatively long, suggesting that water may not play a significant role in the higher thermodynamic stability of 2%-O-methyl RNA relative to RNA [23]. This initial finding at medium resolution was later confirmed by the crystal structure of the fully 2%-O-methylated RNA duplex with the sequence CGCGCG determined at 1.3 A , resolution [72]. Thus, the minor groove of the modified duplex featured only a relatively small number of water molecules.…”
Section: Structural Properties Of 2%-o-modified Rna Analoguesmentioning
confidence: 99%
“…Five high-resolution crystal structures of magnesium compounds with [r{2'-O -Me(CGCGCG)}] 2 ( P 6 1 22 form [ 77 ] and P 3 2 [ 80 ] , and r(GGUGAGG)·r(CCUCACC) [ 81 ] are reported. Mg 2+ ions directly bind to the phosphate groups connecting neighboring duplexes [ 77 ] or act as an anchor attached to the 3'-terminal G [ 79 ] .…”
Section: +mentioning
confidence: 99%
“…Mg 2+ ions directly bind to the phosphate groups connecting neighboring duplexes [ 77 ] or act as an anchor attached to the 3'-terminal G [ 79 ] . Hydrated metal ions are located preferably in the major groove [77][78][79][80][81] compared to the minor groove [ 81 ] , and when they are located in the major groove, the formation of outersphere N7···O(W)-M-O(W)···O6 bonding at the guanine residue is prominent [78][79][80][81] .…”
Section: +mentioning
confidence: 99%